Kebijakan Green Economy melalui Sektor Energi Terbarukan dalam Pencapaian SDGS: Tinjauan Pustaka Sistematis - Susanti, Anita; Meilany Nabila, Zahra; Nuriansyah, Fazar; Imani Hakam, Lazuardi (Jurnal Ekonomis, 2025)
The rapid economic development and increasing energy consumption have posed significant challenges to global environmental and social sustainability. The dominance of fossil energy has led to an increase in carbon emissions, making the transition to a green economy and the use of renewable energy critical solutions for achieving the Sustainable Development Goals (SDGs), particularly SDG 7 on affordable and clean energy. This study analyses green economy policies in achieving SDGs through the renewable energy sector using the Systematic Literature Review (SLR) method. Based on 12 articles analysed, the main findings show that green economy policies, through the development of renewable energy and green finance, positively impact sustainable economic growth and carbon emission reduction in various countries. Furthermore, the increase in renewable energy consumption has also been shown to support the reduction of social inequalities and improve welfare. This study provides strategic recommendations for Indonesia to strengthen green economy policies, particularly in the renewable energy sector, to achieve more optimal SDGs.